2006
DOI: 10.1029/2005je002653
|View full text |Cite
|
Sign up to set email alerts
|

Phase dispersion relation of the 5‐micron hot spot wave from a long‐term study of Jupiter in the visible

Abstract: [1] We present a long-term study at visible wavelengths of the motions and spatial distribution of the hot spots at 7°N of Jupiter. This research involves seven years of observations of the planet between 1979 and 2002 and includes data from Voyagers 1 and 2, Hubble Space Telescope, and a number of ground-based observatories. Our analysis of the North Equatorial Belt (NEB) dark projections (DPs) velocities and wave numbers showsthatadispersionrelationship exists,withtheDPsvelocity(rangingfrom97to113ms À1 ) sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 40 publications
4
32
1
Order By: Relevance
“…From our measurements of the movement of the different dark projection groups we obtained the dispersion relationship shown in Fig. 3 [3]. Interestingly these values are similar to the ones that Ortiz et al [4] found when studying the hot spots movement in the IR.…”
Section: Hot Spotssupporting
confidence: 73%
“…From our measurements of the movement of the different dark projection groups we obtained the dispersion relationship shown in Fig. 3 [3]. Interestingly these values are similar to the ones that Ortiz et al [4] found when studying the hot spots movement in the IR.…”
Section: Hot Spotssupporting
confidence: 73%
“…The main article covers two newly-identified wave patterns in the 0-30 • N domain, but the data presented throughout the article also shows thermal contrasts associated with a third wave on the prograde NEBs jet between 6-9 • N. This pattern of visibly-dark, longitudinallyelongated 'hotspots' and adjacent bright fans of material (referred to as plumes, although these are not always associated with convection) that can be seen near 8 • N in reflected sunlight [Allison, 1990;Baines et al, 2002;Arregi et al, 2006;Choi et al, 2013], infrared [Or- Fletcher et al, 2016], and radio-wave observations [de Pater et al, 2016;Cosentino et al, 2017]. This chain moves slowly westward with respect to the rapid eastward flow of the NEBs, and has been interpreted as an equatorial Rossby wave pattern [Showman and Ingersoll, 1998;Showman and Dowling, 2000;Friedson, 2005], with rising air and condensation in the plumes and descent and aerosol-clearing in the hotspots.…”
Section: A4 Supplemental S4: the Nebs Wavementioning
confidence: 99%
“…Note that this section does not deal with the trapped equatorial Rossby wave pattern on the NEBs [and its associated hotspots and plumes, Allison, 1990;Ortiz et al, 1998;Showman and Dowling, 2000;Baines et al, 2002;Friedson, 2005;Arregi et al, 2006;Choi et al, 2013].…”
Section: A2 Supplemental S2: Previous Detections Of Mid-neb Wavesmentioning
confidence: 99%
“…(1) the South Temperate Belt was faded, except for a turbulent sector extending about 80 • in longitude, with a detached oval BA characterized by its ringed structure and the accompanying small, dark cyclone and short turbulent area; (2) there was a well-developed gray belt in the STrZ contiguous to the SEB, making this belt appear wider in latitude than it usually is; (3) the SEB was fully recovered as a low albedo band from its last fade (Pérez-Hoyos et al 2012); (4) no large and conspicuous "dark projections" were present at the equatorward edge of the NEB (these are the low-albedo visible counterparts to the 5-μm hot spots; Arregi et al 2006). We show that this is an important aspect affecting the wind profile; (5) on the NEB poleward side, three large barges dominate the scene (about five in total were present); (6) the north tropical zone (NTrZ) was a prominent zone, but the NTB was faint with small-scale features.…”
Section: Jovian Cloud Morphology In the September-december 2011 Periodmentioning
confidence: 99%